Handbook of research on teaching - Gitomer, Drew H.; Bell, Courtney A. (Washington, D.C. : American Educational Research Association, 2016)
'The Fifth Edition of the Handbook of Research on Teaching is an essential resource for students and scholars dedicated to the study of teaching and learning. The volume covers a vast array of topics ranging from the history of teaching to technological and literacy issues. In each authoritative chapter, the authors summarize the state of the field while providing a conceptual overview of a critical aspect of research on teaching. Each of the volume's 23 chapters is a canonical piece that will serve as a reference tool for the field. The chapters, all broad treatments of areas of study, will help readers see how particular areas of research connect with the larger issues of teaching and teacher education. The Handbook, therefore, provides readers with a'20,000-foot view' of the current state of education research.' -- Publisher's description.
Thinking philosophically about teaching / Gert J.J. Biesta and Barbara S. Stengel -- In search of a grand narrative : the turbulent history of teaching / Judith Kafka -- Engaging methodological pluralism / Pamela A. Moss and Edward H. Haertel -- Teaching beyond achievement tests : perspectives from developmental and education science / Elise Cappella, J. Lawrence Aber, and Ha Yeon Kim -- The sociopolitical context of teaching / Na'ilah Suad Nasir, Janelle Scott, Tina Trujillo, and Laura Hernandez -- What constitutes teacher learning? / Rosemary S. Russ, Bruce L. Sherin, and Miriam Gamoran Sherin -- Research on teacher preparation : charting the landscape of a sprawling field / Marilyn Cochran-Smith and Ana Maria Villegas with Linda Whalen Abrams, Laura C. Chavez-Moreno, Tammy Mills, and Rebecca Stern -- Preparing teachers for teaching in and advocating for linguistically diverse classrooms : a vade mecum for teacher educators / Christian J. Faltis and Guadalupe Valdes -- Teaching diverse learners / Prudence L. Carter and Linda Darling-Hammond -- Teaching students with special needs in the new millennium / Janette Klingner, Mary Brownell, Linda H. Mason, Paul T. Sindelar, and Amber Benedict with Cynthia Griffin, Kathleen Lane, Maya Israel, Wendy Peia Oakes, Holly Mariah Menzies, Kathryn Germer, and Yujeong Park -- Teachers and teaching in the context of globalization / Lynn Paine, Sigrid Blomeke, and Olena Aydarova -- Assessment and teaching / William R. Penuel and Lorrie A. Shepard --
Includes bibliographical references and indexes.
Keywords: Education -- Research -- United States